Alcaligenaceae and Chromatiaceae as potential pollution bioindicators in palm oil mill effluent and its relationship with environmental parameters and zero-emission system - Mohamad Zainal, Noor Shaidatul Lyana (2020)
Alcaligenaceae and Chromatiaceae have previously identified as unique pollution bioindicators in rivers polluted by palm oil mill effluent (POME) final discharge. Since bacteria are sensitive towards environmental stresses, it is crucial to evaluate survivability of both bacteria in different environmental parameters, proving their credibility as POME pollution bioindicators. Therefore, the effects of temperature (25 – 40°C), pH (7 – 9), durations of UV irradiation (30 – 120 minutes) and during low/high crop seasons of oil palm towards Alcaligenaceae and Chromatiaceae were assessed in the first objective of this study. The POME samples were collected from the facultative pond, algae (aerobic) pond and final discharge point. Following the recent breakthrough in POME management where the zero-emission technology was being introduced, the second objective of this study was conducted to evaluate the implementation effect of the zero-emission of POME final discharge towards bacterial community dynamics in a constructed artificial river water system. For both objectives, the viability status and composition of bacterial community were assessed using flow cytometry-based assay and 16S rRNA amplicon sequencing using Illumina MiSeq, respectively, in correlation with the changes of physicochemical properties. The shifts of physicochemical properties, nutrient contents and bacterial community dynamics were correlated using principal coordinate (PCO) analysis. Even though the changes of environmental parameters changed the physicochemical properties, as well as the viability and nucleic acid contents of bacterial cells in POME, the Alcaligenaceae and Chromatiaceae remained detected in all POME samples, each comprising more than 0.5% from the total bacterial population, and thus could be regarded as the reliable bacterial indicators. Both were shown to be positively correlated with biological oxygen demand (BOD5); hence they could be used in complementary with the current adopted physicochemical assessment to specifically indicate the contaminated river due to POME final discharge. Following the implementation of zero-emission of POME final discharge, the polluting properties of the affected river water were reduced, as shown by the physicochemical properties, nutrient contents and bacterial cell’s viability (from 43.0% to 24.5%). Being the bacterial indicators to detect the presence of POME final discharge in the river water, Alcaligenaceae and Chromatiaceae were shown to be carried over by the effluent into the artificial river water system with total bacterial compositions of 1.0 – 1.3% and 2.2 – 5.1%, respectively. As a result of the implementation of zero-emission system, the Chromatiaceae was shown to be reduced from 2.2% on day 8 until it was undetected on day 15. Even though still being detected after the zero-emission system implementation, Alcaligenaceae was constantly reduced from 1.2% on day 8 to 0.9% on day 15. The positive correlation between both Alcaligenaceae and Chromatiaceae and BOD5 had strengthen the possibility of further reduction of Alcaligenaceae with the reduction of contamination level, indicated by BOD5. Overall, it can be concluded that the Alcaligenaceae and Chromatiaceae showed to be the reliable POME bacterial indicators despite the changes of environmental conditions. Their reduction following the implementation of zero-emission also proved the efficiency of zero-emission system in reducing the polluting properties of the affected river water.